PUBLIC-PRIVATE PARTNERSHIP IN MICROFINANCE - Nataliya Sokrovolska; Oksana Prodius; Olena Zhuk; Galyna Yamnenko; Vita Fedyna (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The aim of the article was to determine the distinctive features of the design and implementation of public-private partnership in microfinancing. The study involved the following methods: synthesis was used to identify trends in the development of the microfinance market and analyze innovative approaches to managing microfinance programs; statistical analysis for regression analysis of factors influencing the effectiveness of the implementation of microfinance programs in financial and social aspects. The methodological background of the analysis is the Data Envelopment Analysis, which is linear programming used to determine the separate and joint impact of factors on the performance of microfinance organizations, as well as to quantitatively assess this influence. Prospects for future research include an extended study of exogenous and endogenous factors influencing microfinance programs in both Vietnam and the Southeast Asian region.